Spatial Evaluation of Waste Disposal Site Selection Using GIS-Based Multi-Criteria Analysis: A Case Study of Dera Ghazi Khan District, Pakistan - Rehman, Aneeq Ur; Ahmad, Adeel; Sadef, Yumna; Ahmad, Sajid Rashid (Indonesian Journal of Geography, 2024)
The rapid population growth and rising per capita incomes have caused the city to generate massive amounts of municipal waste, indicating a serious environmental threat. Solid waste disposal has become a crucial problem for several municipalities. The selection of suitable waste disposal sites is a crucial problem in the urban areas of developing countries like Pakistan due to unsatisfactory urban planning and management to decrease human being’s health risks. Particularly, Dera Ghazi (D.G.) Khan district is facing the issue of identifying suitable sites for solid waste disposal. This research aims to select appropriate potential sites suitable for solid waste disposal purposes in the D.G. Khan. Primary datasets used for this study are Landsat-8 satellite imagery, digital elevation model (DEM) with 30-meter resolution for slope extraction. Other criteria included roads, railroads, and rivers digitized using the topographical map of the study area. The maps are prepared to incorporate overlay and suitability analysis using Geographic Information System (GIS), Remote Sensing techniques, and Analytical Hierarchy Process (AHP), a multi-criteria analysis. The final suitability map of study area is prepared using a GIS software suite and categorized as highly, moderately, least, and unsuitable regions, of which 3% is entirely unsuitable area, 70% less suitable, 26.16% moderately suitable, and 0.84% highly suitable area. The suggested disposal sites have been carefully selected to assist policymakers in determining the most sensitive areas and resolving waste management issues with the slightest contamination of water bodies and the environment.